Neurolinguistics and language function - Kamaruddin, Rohaidah; Seruji, Zuraini; Mohd Noor, Atikah; Mat Yassin, Nur Marjan; Yajib, Siti Izarina (David Publishing Company, 2018)
Neurolinguistics is known as a study of relationship between brain and language. Human brain consists of three main parts such as forebrain (crucial part), midbrain (the smallest part), and hindbrain (the lowest part). Basically, human language centre is located in frontal lobe of human brain where the left and the right hemisphere are located. Language use sometimes is more dominant in the left hemisphere although the right hemisphere functions for language. Specifically, the areas that are involved in language are frontal lobe (Broca) and temporal lobe (Wernicke). The lesion on brain will scientifically cause language disorder which is known as aphasia. The types of aphasia are Broca’s aphasia, Wernicke’s aphasia, pure word deafness aphasia, conduction aphasia, anomic aphasia, apraxia aphasia, global aphasia, and aphasia reading and writing (dyslexia). The physical condition of a healthy brain is very important to prepare the activities of thinking and acting. Thus, the brain must be protected appropriately.